TELAAH KONSEP MANAJEMEN STRATEGIK ANTARA PORTER DAN HAMEL DAN PRAHALAD - Johny Rusdiyanto (Journal of Management and Business, 2002)
There is little question that strategic management is undergoing profound perspective change as the 21st draw to close. What are the forces for change? Where are strategic management going? What are the obstacles to getting there? These are the questions I propose to discuss in this paper. In order to maintain the existence of an organization, the role of strategic management more crucial in many organizations. On one hand, the strategic management is have to be fermulated with high adaption to environment changes and match with their own core capabilities. On the other hand, organizations have an precendented opportunity to refocus their internal activities system as strategic assets. Transforming this conditions into an opportunity, however, requires a new strategic management perspective, especially to formulate the matching strategy. The world is surprised because of new perspective in Strategic management that have specific description.The two perspectinves of strategic management socialized by Michael Porter and Hamel and Prahalad. These two perspectives inspires strategist to find the right strategic concept before their formulate the right strategy for their company. This paper describe and clarify the focus, color and the specific implementation of Porter and Hamel and Prahalad perspective on Strategic Management.